Pengawasan Akuisisi Saham di Indonesia: Sistem Post Notification dalam Perspektif Persaingan Usaha - Elisabeth Dian Aprilliani; Arief Suryono (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2026)
This study examines thee regulations governing the post-notification obligation for share acquisitions from the perspective of competition law in Indonesia, as well as efforts to optimise it as an effective supervisory instrument. Indonesia adopts a post-notification system as stipulated in Law No. 5 of 1999 and its implementing regulations, which require business entities to report acquisition transactions to the KPPU after the transaction has taken effect. Although this system provides flexibility for business entities, in practice there are a number of weaknesses, including its reactive nature, low levels of compliance, and limitations in the effectiveness of oversight in preventing anti-competitive effects. This study employs a normative legal method using legislative, conceptual, and comparative approaches, as well as an analysis of KPPU decisions. The research findings indicate that the post-notification system is not yet optimal in maintaining healthy business competition. Therefore, there is a need to strengthen oversight mechanisms, improve business compliance, and update legal policies to be more adaptive, including the possibility of limited integration of pre-notification elements. It is hoped that these optimisations will enhance the effectiveness of acquisition control and prevent monopolistic practices and unhealthy business competition in Indonesia.